SISTEM ADAT PERKAWINAN DI DESA PARIT BARU KECAMATAN TAMBANG KABUPATEN KAMPAR - Notalia "; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Indigenous is a variety of conditions or behaviors that should be implemented in social life. This study intends to determine the application of indigenous in Parit Baru communities, this study uses pupsive sampling technique which take an objects based on certain criteria or calculation, to collecting the data observation has done on the phenomena which appear in the customary system of research, interviews is doing a question and answer directly to the informant, the documentation is to collect all the information relating to the problems examined in the form of notes, photos and so forth. From the research found that indigenous which applied in peoples of Parit Baru was hampered which lead to changes in customs itself, which is of influence of technology, changes in the pattern of relationships and family.Keywords: Indigenous and pupsive sampling